Covid-19 Effects on ARTErial StIffness and Vascular AgeiNg: CARTESIAN Study Rationale and Protocol - Bruno, Rosa Maria; Spronck, Bart; Hametner, Bernhard; Hughes, Alun; Lacolley, Patrick; Mayer, Christopher C.; Muiesan, Maria Lorenza; Rajkumar, Chakravarthi; Terentes-Printzios, Dimitrios; Weber, Thomas; Hansen, Tine Willum; Boutouyrie, Pierre (Artery research, 2020)
In December 2019, an outbreak of pneumonia caused by a novel Coronavirus (COVID-19) spread rapidly worldwide. Although the clinical manifestations of COVID-19 are dominated by respiratory symptoms, the cardiovascular system is extensively affected at multiple levels. Due to the unprecedented consequences of the COVID-19 pandemic, the ARTERY society decided to launch the Covid-19 effects on ARTErial StIffness and vascular AgeiNg (CARTESIAN) study — the first international multicentre study into the effects of COVID-19 on non-invasive biomarkers of vascular ageing. The main study objective is to evaluate the presence of Early Vascular Ageing (EVA) 6 and 12 months after COVID-19 infection. Secondary objectives are to study the effect of COVID-19 disease severity on EVA, to investigate the role of psychosocial factors in COVID-19 induced EVA, and to investigate the potential modifying effect of comorbidities and chronic treatments. In the CARTESIAN study, a broad array of cardiovascular measurements, including carotid-femoral pulse wave velocity, central blood pressure, carotid ultrasound, brachial flow-mediated dilatation, will be performed. To date, 43 centres from 21 countries have agreed to participate, with an expected study population of >2500 individuals. To our knowledge, CARTESIAN will be the first study to provide insight into the relationship between COVID-19, its severity, and early vascular ageing in a large cohort, potentially enabling future care and diagnostics to be more focused on the most vulnerable.